Prevention of respiratory syncytial virus infection - Samson, L (Pulsus Group Inc, 2009)
Respiratory syncytial virus (RSV) infection is the leading cause of lower respiratory tract infection in young children, with significant numbers of premature infants and those with other risk factors requiring hospitalization in Canada each year. Palivizumab, an RSV-specific monoclonal antibody, can reduce the hospitalization rate and severity of illness for a small group of high-risk or premature infants during their first RSV season. The present statement reviews the published literature and provides recommendations regarding its use in premature and other at-risk infants, for Canadian physicians.